2006
DOI: 10.1128/mcb.02185-05
|View full text |Cite
|
Sign up to set email alerts
|

GAS41 Is Required for Repression of the p53 Tumor Suppressor Pathway during Normal Cellular Proliferation

Abstract: GAS41 is a common subunit of the TIP60 and SRCAP complexes and is essential for cell growth and viability. Here, we report that GAS41 is required for repression of the p53 tumor suppressor pathway during normal cellular proliferation. Either GAS41 small interfering RNA-mediated knockdown of GAS41 expression or specific interruptions of the carboxy-terminal coiled-coil motif of the GAS41 protein activate the p53 tumor suppressor pathway, as evidenced by p53 up-regulation, p53 serine-15 phosphorylation, and p21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
70
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 50 publications
5
70
0
Order By: Relevance
“…Amplified copy numbers of the GAS41 (glioma-amplified sequence) gene have been observed in glioblastoma multiforme and astrocytoma (Fischer et al, 1997). More recently, GAS41 has been implicated in suppression of the p53 tumour suppressor pathway during normal cell growth (Park and Roeder, 2006). Like Tip60 itself, the NuA4 subunits BAF53a, TRRAP and p400 have been implicated in c-Myc oncogene-mediated cellular transformation (Fuchs et al, 2001;Nikiforov et al, 2002;Park et al, 2002).…”
Section: Tip60-associated Proteins and Their Links To Cancermentioning
confidence: 99%
“…Amplified copy numbers of the GAS41 (glioma-amplified sequence) gene have been observed in glioblastoma multiforme and astrocytoma (Fischer et al, 1997). More recently, GAS41 has been implicated in suppression of the p53 tumour suppressor pathway during normal cell growth (Park and Roeder, 2006). Like Tip60 itself, the NuA4 subunits BAF53a, TRRAP and p400 have been implicated in c-Myc oncogene-mediated cellular transformation (Fuchs et al, 2001;Nikiforov et al, 2002;Park et al, 2002).…”
Section: Tip60-associated Proteins and Their Links To Cancermentioning
confidence: 99%
“…For the purification of p400 complexes from HeLa cells that stably express Flag-p400 and HA-TIP60, nuclear extracts were prepared by a modified Dignam procedure and directly applied onto a Sepharose CL6B gel filtration column to remove unincorporated free HA-TIP60 (23). Fractions corresponding to the p400 protein peak, as determined by immunoblotting, were combined and subjected to M2 agarose affinity purification.…”
Section: Methodsmentioning
confidence: 99%
“…Chromatin immunoprecipitation (ChIP) assays were conducted as described previously (23). Briefly, 10 7 cells were cross-linked by the direct addition of formaldehyde (final concentration, 1%) to cells for 10 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Because YEATS domain-containing proteins are found in chromatin-modifying and transcription regulatory complexes, this domain is proposed to function in histone and chromatin interactions (18). We previously reported that GAS41 plays a role in repressing the p53 tumor suppressor and appears to reside in a different complex that is independent of the GAS41-containing TIP60 and SRCAP chromatin-remodeling/modifying complexes (19). Here we report the identification of a novel GAS41-PP2C␤ complex that shows phosphatase specificity for phosphorylated serine 366 of p53.…”
mentioning
confidence: 99%
“…Protein Purification-For purification of GAS41-PP2C␤ complexes from 293T cells that stably express FLAG-GAS41, nuclear extracts were prepared by a modified Dignam procedure and directly applied to a Sepharose CL6B gel filtration column to remove GAS41-containing nuclear chromatin-remodeling complexes (19). The fractions corresponding to the GAS41 protein peak around 158 kDa of apparent molecular mass were combined and subjected to M2 agarose affinity purification.…”
mentioning
confidence: 99%